MARKETING MIX STRATEGY IN MAINTAINING BUSINESS EXISTENCE FOR EXPATRIATES DURING THE COVID-19 PANDEMIC - Yamawati Ni Kd Sioaji; Dewi I Gusti Ayu Ratih Permata; Pratama I Gede Agung Wira (International Journal of Social Science, 2022)
Tourism is an industry with strong links to other sectors as tourism can be characterized as a combination of phenomena and interrelationships through interactions with tourists, business suppliers, destination governments and destination communities. Much likely to what is happening around the world, Bali's tourism industry is also in decline due to the coronavirus pandemic. The impact is being experienced by Small and Medium Enterprises (SMEs) in the tourism services industry across various sectors, with the tourism sector itself has been experiencing losses of around Rp9.7 trillion monthly. This study was conducted at Parklife-Family Hub Bali, Canggu using a random sampling method with all customers as respondents. The analytical technique used in this study is Structural Equation Modeling (SEM) by using Partial Least Squares (PLS) approach with Smart PLS 3.0 program tool. Data analysis revealed that the variables of People, Physical Evidence, Price, Process, Product, and Advertising have a positive and significant impact on the company's existence, while the Location has a negative and non-significant impact on the business existence means that it does not play an important role in the existence of firms.